UV-C Disinfection in the Environment of Pathogen Transmission - Kasemsap, Charuvan (Journal of Food Health and Bioenvironmental Science, 2023)
Coronavirus disease 2019 (COVID-19) is a respiratory infection caused by SAR-COV-2 (COVID-19 virus). COVID-19 typically rapidly spread from one person to another via respiratory droplets (>5-10 μm in diameter) during coughing and sneezing or touch. Thus, environmental surfaces should be frequently cleaned with water, detergent, and followed by application of disinfection as chemical disinfectants and physical disinfection. Ultraviolet germicidal irradiation (UVGI) is the use of ultraviolet energy to inactivate viral, bacterial, and fungal species because the UVC directly damages deoxyribonucleic acid (DNA), Ribonucleic acid (RNA), and also prevent the bacterium from being viable. The most effective wavelength is in 245 -285 nm. Conventional ultraviolet disinfection consists of a mercury amalgam, which is a hazardous material to the environment. In addition, excessive exposure causes sunburn skin, skin cancer and damage to the corneas of the eyes. Therefore, the risk management such as enclosure cabinets, indicator warning sign light, and personal protection equipment (PPE) should be considered.